RNF180 weakened the lipid droplet formation and subsequent chemoresistance by destabilizing ACC1 and ACLY in esophageal cancer - Ning Li; Dao-Fu Shen; Nan-Chang Yin; Zheng-Guo Cui; Hua-Chuan Zheng (Frontiers in Pharmacology)
ObjectiveRNF180 (Ring finger protein 180) is an E3 ubiquitin-protein ligase that promotes polyubiquitination and proteasomal degradation. The study aimed to clarify the clinicopathological significances, signal pathways and molecular mechanisms of RNF180 expression in esophageal cancer.MethodsWe analyzed the clinicopathological significances and signal pathways of RNF180 expression in esophageal cancer (EC) through bioinformatics and pathological analysis. We also clarified its effects on aggressiveness and related molecular mechanisms in vitro.ResultsRNF180 mRNA expression was lower in EC than in normal tissues (p < 0.05), opposite for its methylation (p < 0.05). RNF180 mRNA expression was negatively correlated with its promoter methylation, but positively with high histological grading, N stage, and poor prognosis of EC (p < 0.05). RNF180 protein expression was positively associated with T stage, N stage, and TNM stage, but negatively with unfavorable overall survival of EC as an independent factor (p < 0.05). The differential genes of RNF180 can be categorized into olfactory transduction, focal adhesion, vascular smooth muscle contraction, calcium signal pathway, cell adhesion molecules, muscle contraction, ECM receptor interaction, and collagen degradation (p < 0.05). RNF180-related genes can be categorized into gastric acid and insulin section, muscle and cardiomyopathy, glycoprotein binding, collagen and extracellular matrix, fat digestion and diabetes, PPAR signal pathway and peptidase activity. RNF180 overexpression reduced proliferation, migration, invasion and epithelial-mesenchymal transition, and induce mitochondrial apoptosis, and Caspase-1-dependent pyroptosis of EC cells (p < 0.05). RNF180 might induce chemosensitivity by weakening ACC1- and ACLY-mediated lipogenesis via the ubiquitination and proteasomal degradation of ACC1 and ACLY, and lipid droplet assembly.ConclusionRNF180 might be considered as a biological marker for aggressive behaviors and poor prognosis in EC and as a molecular target of gene therapy.